Expressão de genes de mediadores citotóxicos por CMSP tratadas com pastas endodônticas indicadas para dentes decíduos - Nakashima, Brenda Lanza (2015)
Iodoform (PI) and calcium hydroxide- based pastes (PH) are used in pulpectomy of primary teeth, complementing the antimicrobial action of mechanical chemical preparation and promoting tissue repair. These pastes take up and stay for a period of time along the root canal by contacting the periapical region and surrounding tissue, making it the aim of this study to quantify the relative expression of toxicity genes expressed by pastes, evaluating the biocompatibility these materials. By RT-PCR assay, were analyzed cellular mechanisms induced or generated by extracts of endodontic pastes: PI with Nebacetin (PNEB); with Maxitrol (PMAX); chlorhexidine (PCHX); and Guedes Pinto (GP); and PH: Calen® thickened with zinc oxide ( Calen®/ZO); and calcium hydroxide paste with Chlorhexidine (PHCHX); Ultracal®XS, using mononuclear cells from human peripheral blood (PBMC) , for to quantify the gene expression on the cytotoxic mediators: Granzyme A, Granzyme B, Granulysin and Perforin. Prior to gene expression, to analyze aspects of cell viability assays were performed - MTT, LDH and Capases Activity. The results were analyzed by Kolmogorov-Smirnov, one-way ANOVA and Tukey test, with p<0.05. The PNEB was the only one among all evaluated pastes that expressed all cytotoxic mediators above mentioned (p<0.05). Reviewed in cell viability, increased by PNEB Caspases 1 and 8 (p<0.05); The PGP increased Caspases 1, 3 and 8 (p<0.05); The PCHX decreased cell viability MTT and LDH, and exhibit increased activity of all Caspases (p<0.05). In PH, Ultracal®XS only presented significant concentration values for Caspase 1 , 3 and 8 (p<0.05). Despite the PNEB have presented high relative gene expression of all cytotoxic mediators analyzed, not caused decrease in cell viability, not causing increased activity of Caspase 3 (effector of apoptosis), demonstrating biocompatibility. Among the PI that showed better biocompatibility under the aspect of cytotoxicity were the PGP and PMAX. The material with cytotoxic potential observed in this experiment was the PCHX as dramatically decreased cell viability, confirmed the two tests and supported by high activity of all the analyzed Caspases, and also due to cell death, the inability of gene expression. All pH played citocompatível behavior, according to tests performed in the light of molecular biology.